System Development For Low Cost Data Acquisition For Mobile Satellite Signal Performance Measurement In Low-Latitude - I., Abba; W.A.W.Z, Abidin; T., Masri; K.H, Ping; M.S, Muhammad; B.V, Pai (International Journal Of Scientific & Technology Research, 2014)
Mobile Satellite (MS) Signal performance is affected by many factors such as ionospheric effect, multipath fading tree-shadowed and buildingshadowed. These cause variations in the received signal quality. Although many studies have been carried out in order to improve the performance of MS signal, there are still many areas lacking data especially from the less-developed and developing countries. Furthermore, costly data acquisition method hinders more study to be carried out in these regions. This paper discusses the cost effective alternative method for MS data acquisition for satellite operating in the L-band by utilizing the GPS satellites data. Details methodology for doing the experimental works will be discussed. The measurements of the signal performance are performed for open space environment in Sarawak. The analysis of the signal performance under different MS environments is performed with respect to the information such as elevation and azimuth angles. The analysis produced forms an important part in the studies of the signal performance. From this research work, we characterized the MS received signal for Sarawak.